Genetics and demography of kelp gulls in Patagonia - Lyons, Amanda (2015)
The Kelp Gull (Larus dominicanus), a common seabird in coastal Patagonia, has recently increased in overall abundance and distribution, creating some concerns for the protection and conservation of other native, threatened species. We combined genetic and demographic data of four large Kelp Gull colonies distributed along 1800 km of the northern Patagonian coast of Argentina to further understand patterns of population growth and migration of the species. DNA analysis of variable intron sequences of two separate genes (myelin proteolipid protein, β-fibrinogen) revealed similar intra-colony levels of DNA sequence diversity. Pairwise FST comparisons revealed significant differentiation of the northernmost colony, Islote La Pastosa, from the two southern colonies, Punta Tombo and Isla Vernaci Sudoeste (p < 0.05). Indirect estimates of gene flow suggest significant mixing among colonies (Nm > 6). Demographic estimates revealed that Islote La Pastosa showed an increase in the number of breeding individuals over time (λ = 1.075), representing an area of potential population expansion. This is consistent with previous studies that have suggested that the demographic connectivity among Kelp Gull colonies in Patagonia may follow a source-sink dynamics, where growth rates of growing colonies are fuelled by the immigration of individuals from nearby colonies. The observed pattern also reflects the overall expansion of the species in the Patagonian region. This study suggests that proper management strategies for the Kelp Gull should take into account the genetic and demographic dynamics of this species.